Consecutive Macular Edema and Visual Outcome in Branch Retinal Vein Occlusion. (22nd May 2014) - Baek, Sung Uk; Kwon, Soon Il; Park, In Won; Choi, Kyung Jun
Abstract : Purposes . The study introduced the concept of "consecutive macular edema" and evaluated the validity of visual outcome in macular edema (ME) secondary to branch retinal vein occlusion (BRVO). Methods . Patients were categorized into the gainer group and the nongainer group according to the final visual acuity. We analyzed clinical characteristics involving total and consecutive duration of ME between the two groups. Results . Among the total 71 eyes of 71 patients, intravitreal bevacizumab injection (26 patients), triamcinolone (21), and natural course (33) were enrolled. The consecutive duration of ME was shorter in the gainer group than in the nongainer group (3.33 ± 1.50 and 5.24 ± 2.39 months; P = 0.000 ). After exclusion of macular ischemia, consecutive duration of ME in gainer group was also significantly shorter than in nongainer group (3.62 ± 1.60 and 6.11 ± 4.20 months; P = 0.010 ). Conclusions . The duration of ME in the nongainer group was longer than in the gainer group. In particular, the consecutive duration was an important factor in determining the final visual outcome. Clinical Trial Registration . Approval by Hallym University Sacred Heart Hospital Institutional Review Board/Ethics Committee was obtained for this retrospective study.